PENGARUH JARAK TANAM DAN WAKTU PENYIANGAN TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium salonicum L .) PADA LAHAN ULTISOL DI KABUPATEN BANGKA - Kusmiadi R; Ona C; Saputra E (Enviagro: Jurnal Pertanian dan Lingkungan, 2015)
The research aimed to find the appropriate plant spacing and weeding period to onion growth and production in ultisol land. Furthermore, the objective of the research is to identify interaction between plant spacing and weeding period and its effect to onion growth and production. The experiment conducted in May 2014 – July 2014 in Experimental Field, Faculty of Agriculture, Fisheries and Biology, Bangka Belitung University. It used Factorial Completely Randomized Design with two factors and three repeated. First factor is plant spacing, consist of J1 (10 x 15 cm) and J2 (20 x 15 cm). Second factor is weeding period, consist of P0 (without weeding), P1 (weeding in 7 day after palnting), P2 (weeding in 14 day after palnting), P3 (weeding in 21 day after palnting), P4 (weeding in 28 day after palnting), P5 (weeding to harvest time). The result showed plant spacing 20 x 15 cm and weeding period until harvest time give the great result to onion growth and production. Furthermore, it showed that no interaction between plant spacing and weeding period